EXERGETIC ANALYSIS OF A SOLAR PHOTOVOLTAIC TRACKING SYSTEM IN ERBIL, IRAQ - MOLAN, MAHDE AKRAM; HAMAKHAN, IDRES AZZAT; M.SHAREEF, SARKAR JAWHAR (Journal of Duhok University, 2017)
This paper investigates exergy analysis of a solar photovoltaic system that is designed, constructed and tested in Mechanical engineering department, Salahaddin University-Erbil 36°14″N, 44°01′E. Exergy analysis is used to estimate the exergy destruction losses during the PV module conversion process by using the second law of thermodynamics and to refine and predict the variations in solar photovoltaic behaviour. The electrical and operating considerations of a photovoltaic module include total solar irradiation, maximum generated power by the system, voltage, open-circuit voltage, current, short circuit current, cell temperature, and ambient temperature. To find sun’s position in the sky LDRs (light dependent resistors) are used as an input feedback and rotate the PV module to track the sun using motors and actuators. Quantity of four LDRs mounted on the solar tracking system frame used to find the light intension difference between all four directions north, south, east and west. The system is automatically controlled by PLC system and is able to rotate the photovoltaic module to follow altitude angle of the sun between 0o to 90o using a 24 inches 36V DC actuator and a 12V high torque DC motor is used to rotate the photovoltaic module toward east and west to follow the sun’s azimuth angle for 360 degrees. The results show that most of the solar irradiance value is dissipated and not entered to the PV module. However, this dissipation of energy results in decreasing the value of the energy and exergy input to the system. The increase in the value of the energy and exergy losses from the morning to about the noon time is because of increasing of the surface temperature of the solar module. From the output of this work, the authors suggested that the module should be reconstructed and redesigned which is suitable for the Kurdistan environment. The suitable one of the PV is to be designed in a way that the temperature rise within the module is not increased the standard level which is 25 ºC, however the temperature rise is will reach about 50 ºC in the summer. That is why the authors prefer to reconstruct the module.